The Use of Politeness Strategies by Efl Pre-Service Teachers in the Microteaching Class - Iin Rizkiya Fitri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
To analyze the data, I used content analysis by utilizing Brown and Levinson's Politeness theory (1987) as an analytical framework. The organizing stage includes transcription, familiarizing the data, open coding, and interpretation. Data transcription is in the form of written text. Next, the researcher identified relevant parts of the utterance. Then, each utterance was coded and classified into four main politeness strategies according to Brown and Levinson (1987), namely off record, bald on record, positive politeness, and negative politeness. After that, the utterances were categorized into sub categories. The findings are presented in an utterance excerpt and frequency table to provide a clear and systematic. Next, the researcher analyzed the communicative purpose of using the strategy. The final stage is the interpretation of the results, namely, looking for patterns of politeness strategy use and comparing them with previous findings. Finally, three types of politeness strategies were used by EFL pre-service teachers during teaching practicum; these are positive politeness, negative politeness, and bald on record. Positive politeness became the most widely used strategy, with a frequency of 84 this strategy has a percentage of 67,7% of the total data, followed by negative politeness with a frequency of 22 this strategy has a percentage 17,8% of the total data and bald on record with a frequency of 18 this strategy has a percentage 14,5% of the total data. The results showed that pre-service teachers actively used positive politeness strategies to build good relationships with students and create a supportive classroom atmosphere. The findings of this research are in line with Joni and Dharmayanti (2025). The results also showed that pre-service teachers used negative politeness strategies to demonstrate politeness by avoiding the impression of forcing, burdening, or interfering with students' freedom in the learning process. The findings of this research are in line with Amalia (2024). Lastly, the results also showed that pre-service teachers used the bald on record strategy to give direct and clear instructions. The findings of this research are in line with Gede et.al (2021). In conclusion, EFL pre-service teachers actively used three types of politeness strategies during their teaching practicum these are positive politeness, negative politeness, and bald on record. The limitation of this research is that the researcher only takes the data from one of the microteaching class. Apart from that, another limitation is that the video observation of each participant was only taken in one practice. So, further research is recommended to expand the scope of research data collection.
Reupload file repository 20 Februari 2026_Yudi
Keywords: Politeness Strategies; EFL Pre-service Teachers; Microteaching Class